Multi-agent reinforcement learning for flexible shop scheduling problem: a survey - Xu, Weitao; Gu, Jinghan; Zhang, Wenqiang; Gen, Mitsuo; Ohwada, Hayato (Frontiers in Industrial Engineering, 2025)
This paper presents a systematic and comprehensive review of multi-agent reinforcement learning (MARL) methodologies and their applications in addressing the flexible shop scheduling problem (FSSP), a fundamental yet challenging optimization paradigm in contemporary manufacturing systems. While conventional optimization approaches exhibit limitations in handling the inherent multi-resource constraints, dynamics and stochastic characteristics of real-world FSSP scenarios, MARL has emerged as a promising alternative framework, particularly due to its capability to effectively manage complex, decentralized decision-making processes in dynamic environments. Through a rigorous analytical framework, this study synthesizes and evaluates the current state-of-the-art MARL implementations in FSSP contexts, encompassing critical aspects such as problem formulation paradigms, agent architectural designs, learning algorithm frameworks, and inter-agent coordination mechanisms. We conduct an in-depth examination of the fundamental challenges inherent in MARL applications to FSSP, including the optimization of state-action space representations, the design of effective reward mechanisms, and the resolution of scalability constraints. Furthermore, this review provides a comparative analysis of diverse MARL paradigms, including centralized training with decentralized execution, fully decentralized approaches, and hierarchical methodologies, critically evaluating their respective advantages and limitations within the FSSP domain. The study culminates in the identification of significant research gaps and promising future research directions, with particular emphasis on theoretical foundations and practical implementations. This comprehensive review serves as an authoritative reference for researchers and practitioners in the field, providing a robust theoretical foundation and practical insights for advancing the application of MARL in flexible shop scheduling and related manufacturing optimization domains. The findings presented herein contribute to the broader understanding of intelligent manufacturing systems and computational optimization in Industry 4.0 contexts.